Behavior of solid matters and heavy metals during conductive drying process of sewage sludge. Issue 1 (31st December 2016) - Luo, Jianping; Li, Anfeng; Huang, Dan; Ma, Jianju; Tang, Jiqiang
Abstract: Behavior of solid matters and heavy metals during conductive drying process of sewage sludge was evaluated in a sewage sludge disposal center in Beijing, China. The results showed most of solid matters could be retained in the dried sludge after drying. Just about 3.1% of solid matters were evaporated with steam mainly by the form of volatile fatty acids. Zn was the dominant heavy metal in the sludge, followed by Cu, Cr, Pb, Ni, Hg, and Cd. The heavy metals in the condensate were all below the detection limit except Hg. Hg in the condensate accounted for less than 0.1% of the total Hg. It can be concluded that most of the heavy metals are also retained in the dried sludge during the drying process, but their bioavailability could be changed significantly. The results are useful for sewage sludge utilization and its condensate treatment.